Multiple-star wavelength-router network and its protection strategy. - Hill, A.M.
A wavelength division multiplexed (WDM) multiple-star network and its accompanying path and router protection strategies are proposed for interconnecting N major switch nodes in a national-scale telecommunications network. For a single path failure and uniform traffic matrix, fiber requirements are shown to be less than for a WDM ADM ring, while providing greater resilience to multiple path failures. ?Adding? and ?dropping? only whole wavelength channels between node pairs is found to lead to severe design instabilities and overinvestment in fiber, and time-sharing of wavelength channels is recommended to minimize fiber quantities. A star network capable of interconnecting N=22 switch nodes and an all-optical path protection switching method are verified experimentally, using a 16-channel 2,5-Gbit/s WDM system and a 22×22-port bulk-optics wavelength multiplexer as the hub router. Protection switching speeds within 50 ms are projected for a national-scale network
Keywords: 2.5 Gbit/s.; WDM multiple-star network; All-optical path protection switching method; Bulk-optics wavelength multiplexer; Design instabilities; Fiber requirements; Multiple-star wavelength-router network; National-scale telecommunications network; Path protection strategies; Protection strategy; Protection switching speeds; Resilience; Router protection strategies; Single path failure; Star network; Switch nodes; Time-sharing.; Uniform traffic matrix; Wavelength channels